2017
DOI: 10.1016/j.virusres.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

The complete genome sequence of human adenovirus 84, a highly recombinant new Human mastadenovirus D type with a unique fiber gene

Abstract: A novel human adenovirus was isolated from a pediatric case of acute respiratory disease in Panama City, Panama in 2011. The clinical isolate was initially identified as an intertypic recombinant based on hexon and fiber gene sequencing. Based on the analysis of its complete genome sequence, the novel complex recombinant Human mastadenovirus D (HAdV-D) strain was classified into a new HAdV type: HAdV-84, and it was designated Adenovirus D human/PAN/P309886/2011/84[P43H17F84]. HAdV-D types possess usually an oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…Exactly in HAdV-D strains it is often observed that homologous recombination has a driving force in adenovirus evolution (Crawford-Miksza and Schnurr 1996;Gonzalez et al 2015;Ismail et al 2018a;Kaján et al 2017;Robinson et al 2013;Walsh et al 2009). Predominantly, intraspecies recombination events are common, but intergenus recombinants have also been reported already: the head domain of the porcine adenovirus 5 (genus Mastadenovirus) fibre seems to be of atadenoviral origin (Nagy et al 2002), though a porcine atadenovirus has not been discovered yet.…”
Section: Adenovirusesmentioning
confidence: 99%
“…Exactly in HAdV-D strains it is often observed that homologous recombination has a driving force in adenovirus evolution (Crawford-Miksza and Schnurr 1996;Gonzalez et al 2015;Ismail et al 2018a;Kaján et al 2017;Robinson et al 2013;Walsh et al 2009). Predominantly, intraspecies recombination events are common, but intergenus recombinants have also been reported already: the head domain of the porcine adenovirus 5 (genus Mastadenovirus) fibre seems to be of atadenoviral origin (Nagy et al 2002), though a porcine atadenovirus has not been discovered yet.…”
Section: Adenovirusesmentioning
confidence: 99%
“…Human adenoviruses (HAdVs) cause significant numbers of respiratory, ocular, and gastrointestinal diseases and incidences of severe diseases caused by adenoviruses most occur in immunocompromised individuals or toddlers [ 4 , 5 , 6 ]. Recent outbreaks of adenovirus infections are at least partly due to newly evolving adenovirus types from constant HAdVs molecular evolution [ 2 , 7 , 8 ]. To identify these novel clinical isolates is the very first step to study a new pathogen.…”
Section: Introductionmentioning
confidence: 99%
“…Human adenoviruses (HAdVs) are non-enveloped and double-strand DNA viruses which have a diameter of 70–90 nanometers and a genome of 35–40 kb. Currently, 90 genotypes have been identified and classified into seven species (A to G), in which types 1–51 were initially characterized according to serum neutralization and hemagglutination-inhibition tests, whereas types 52 and the other following types were identified using the whole-genome sequence as the typing standard [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. All original serotypes have now been whole-genome sequenced.…”
Section: Introductionmentioning
confidence: 99%